The Effects of Graphic Novels on the Reading Comprehension Scores of Students with Autism Spectrum Disorders (ASD) - Hill, Kristina (My University, 2011)
Students with Autism Spectrum Disorder (ASD) face several challenges in the academic setting. These students often struggle to comprehend what they have read, which makes learning difficult. The purpose of this study was to explore whether the use of selected graphic novels would increase the reading comprehension scores of two students on the Autism Spectrum. The study evaluated the reading comprehension scores of two students with ASD during and after reading selected non-graphic novels. The results were considered. The study then evaluated the reading comprehension scores of these students with ASD during and after reading selected graphic novels. These two sets of scores were then compared.
Thesis (M.S.) University of Wisconsin-Superior, 2011. 36 pages. Includes bibliography and appendix (bibliography pgs. 31-32; appendix pgs. 33-36).
Keywords: Education; Reading; Autism Spectrum Disorder; reading comprehension; Educational Leadership; ASD; graphic novel